Comparison of conventional DCE‐MRI and a novel golden‐angle radial multicoil compressed sensing method for the evaluation of breast lesion conspicuity. Issue 6 (17th November 2016) - Heacock, Laura; Gao, Yiming; Heller, Samantha L.; Melsaether, Amy N.; Babb, James S.; Block, Tobias K.; Otazo, Ricardo; Kim, Sungheon G.; Moy, Linda
Abstract : Purpose: To compare a novel multicoil compressed sensing technique with flexible temporal resolution, golden‐angle radial sparse parallel (GRASP), to conventional fat‐suppressed spoiled three‐dimensional (3D) gradient‐echo (volumetric interpolated breath‐hold examination, VIBE) MRI in evaluating the conspicuity of benign and malignant breast lesions. Materials and Methods: Between March and August 2015, 121 women (24–84 years; mean, 49.7 years) with 180 biopsy‐proven benign and malignant lesions were imaged consecutively at 3.0 Tesla in a dynamic contrast‐enhanced (DCE) MRI exam using sagittal T1‐weighted fat‐suppressed 3D VIBE in this Health Insurance Portability and Accountability Act‐compliant, retrospective study. Subjects underwent MRI‐guided breast biopsy (mean, 13 days [1–95 days]) using GRASP DCE‐MRI, a fat‐suppressed radial "stack‐of‐stars" 3D FLASH sequence with golden‐angle ordering. Three readers independently evaluated breast lesions on both sequences. Statistical analysis included mixed models with generalized estimating equations, kappa‐weighted coefficients and Fisher's exact test. Results: All lesions demonstrated good conspicuity on VIBE and GRASP sequences (4.28 ± 0.81 versus 3.65 ± 1.22), with no significant difference in lesion detection ( P = 0.248). VIBE had slightly higher lesion conspicuity than GRASP for all lesions, with VIBE 12.6% (0.63/5.0) more conspicuous ( P < 0.001). Masses and nonmass enhancement (NME) were more conspicuous on VIBE ( P < 0.001), with a larger difference for NME (14.2% versus 9.4% more conspicuous). Malignant lesions were more conspicuous than benign lesions ( P < 0.001) on both sequences. Conclusion: GRASP DCE‐MRI, a multicoil compressed sensing technique with high spatial resolution and flexible temporal resolution, has near‐comparable performance to conventional VIBE imaging for breast lesion evaluation. Level of Evidence : 3 Technical Efficacy : Stage 3 J. MAGN. RESON. IMAGING 2017;45:1746–1752